Relationship between Teacher Work Motivation and Well-being at Different Stages of covid-19 Lockdown - Liudmyla Karamushka; Oksana Kredentser; Kira Tereshchenko; Gelena Lazos; Alla Klochko (Social Welfare: Interdisciplinary Approach, 2021)
Based on empirical research, the authors show that the first wave of the COVID-19 lockdown (March – June, 2020) had some negative impact on teacher well-being, in particular on such its component as physical health and well-being.